The Role of Sports in Islamic Festivals and Its Relevance to Pluralistic Society: An Analysis from the Prophet Muhammed’s Tradition - Mohammed Ghous Mohammed Insaf; Mohamed Ashath (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2024)
The celebration of Islamic festivals, primarily Eid al-Fitr and Eid al-Adha, traditionally encompasses spiritual practices and communal activities, including sports that foster unity among Muslims and others. However, in contemporary times, the role of sports within these celebrations has diminished, leading to a disconnect from the holistic nature of these festivities as practised during the Prophet Muhammad's (PBUH) time. This paper explores the historical significance of sports in Islamic festivals, drawing upon the Prophet's (PBUH) traditions that emphasise physical activities as an integral part of celebratory events. In contrast, other religious traditions, such as the celebration of Buddha's birthday in Sri Lanka, maintain sports as a central feature of their festival celebrations, often involving diverse communities, including Muslims. This paper argues that reintroducing sports into Islamic festival celebrations can serve as a vital platform for intercultural and interfaith exchanges, enhancing mutual understanding in pluralistic societies. By analysing the potential of sports to bridge communities, this study highlights how such integration can contribute to a more inclusive and harmonious social fabric, aligning with the broader goals of interreligious engagement and cooperation.